Use of Whey Protein Concentrate to Encapsulate Hydrophobic Natural Antimicrobials to Improve Their Incorporation into High Moisture Foods Enhancing Their Antimicrobial Activity - Matiacevich, S (Elsevier Ltd, 2024)
Synthetic antimicrobials have been questioned by consumers; thus, natural antimicrobials have emerged as an alternative. However, their use is limited by their low miscibility in high-moisture foods. The objective of this work was to formulate and characterize microparticles of cinnamaldehyde (E-CIN) and vanillin (E-VA) using whey protein concentrate (WPC), and to assess the effect of the encapsulation on the inactivation of L. innocua in a protein beverage. The concentration of WPC (1:1 or 2:1) in the E-CIN did not affect the droplet size and stability, thus the 1:1 ratio was selected. On the contrary, in E-VA increasing WPC concentration (2:1) reduced the droplet size, increasing stability. E-CIN presented greater antimicrobial activity than the unemulsified CIN. E-CIN (1.0 g/L) showed the greatest antimicrobial activity with 3.5 log cycles reduction of L. innocua. While vanillin encapsulation had an insignificant effect on the antimicrobial activity, reducing 1.0 log cycles of L. innocua. In conclusion, cinnamaldehyde was more effective than vanillin, and the encapsulation with WPC increased its antimicrobial activity. Further research is necessary to improve the stability and the antimicrobial activity of vanillin microparticles. Industrial relevance: This work proposes an alternative to replace synthetic antimicrobials with natural antimicrobials of plant origin. It is based on solving the problem of the low miscibility of hydrophobic antimicrobials such as cinnamaldehyde (cinnamon oil) and vanillin, to incorporate them into foods with high moisture content. This information could be useful for the beverage and juice industry, as encapsulated natural antimicrobials can be used to obtain high-quality, fresh, clean label products. Additionally, extending the shelf life of the product can be advantageous for commercialization purposes. © 2023